Who operates when, where and on whom? A survey of anaesthetic-surgical activity in Ireland as denominator of NAP5. - Jonker, W; Hanumanthiah, D; Ryan, T; Cook, T; Pandit, J; O'Sullivan, E (2014)
The second phase of the 5th National Audit Project of the Royal College of Anaesthetists and the Association of Anaesthetists of Great Britain and Ireland, concerning accidental awareness during general anaesthesia, consisted of a survey of anaesthetic activity in Ireland. A network of consultant anaesthetists co-ordinated data collection from the anaesthetic departments of 46 public and 20 independent hospitals over seven days. Data on patients' characteristics, anaesthetic techniques, staffing, and admission and discharge arrangements were collected on all cases for which anaesthetic care (general, regional or local anaesthesia, sedation or monitored anaesthesia care) was provided. A total of 8049 cases were reported during the survey, giving an annual estimate of 426 600 cases for which anaesthetic care is provided. General anaesthesia constituted 5621 (70%), regional anaesthesia 1404 (17%), local anaesthesia 290 (4%), sedation 618 (8%) and monitored anaesthesia care 116 (1%) of the total number of cases. This survey provides unique data regarding anaesthesia services in public and independent hospitals in Ireland.